Eimeria (Coccidia: Eimeridea) of hares in France: description of new taxa - Aoutil, N.; Bertani, S.; Bordes, F.; Snounou, G.; Chabaud, A.; Landau, I. (Parasite (Paris), 2005)
The oocysts of coccidian of the genus Eimeria were sought in the caecal contents of 46 Lepus granatensis and 18 L. europaeus captured in France. Parasites were found in 34 of the hares. Parasite load was mainly very low. However, species diversity was considerable. 21 species or subspecies were identified, of which 13 species and two subspecies were not previously described. Three of the taxa, E. robertsoni, E. semisculpta and E. townsendi, previously identified on numerous occasions in western Europe and, corresponding to forms or variants created before 1960 that have been subsequently elevated to a specific level, appear to be invalid. Indeed, the parasite descriptions from the material used to effect this modification do not correspond to the original descriptions. A stable equilibrium, as generally observed in the case of many congeneric species co-infection of the same host, was not observed in the hares. This has been attributed to the solitary habits of the host and of the probable polyphyletic nature of the genus Eimeria. Paleontological data for the Leporidae indicate that rabbit parasites are derived from those of the hare. Les oocystes des coccidies du genre Eimeria ont été recherchés dans environ 2 g du contenu caecal de 46 Lepus granatensis et de 18 L. europaeus en France. 34 sont parasités. Ils ont presque toujours une charge parasitaire très faible. La diversité spécifique est néanmoins considérable. 21 espèces ou sous espèces sont identifiées dont 13 espèces et deux sous espèces sont nouvelles. Trois des taxa identifiés plusieurs fois en Europe occidentale : E. robertsoni, E. semisculpta et E. townsendi, qui correspondent à des formes ou à des variétés créées avant 1960 et qui ont été élevées ultérieurement au niveau spécifique, nous semblent inutilisables. En effet, la description du matériel utilisé pour effectuer cette modification ne correspond pas à la description originale. Les équilibres stables constatés habituellement dans les cas de nombreuses espèces congénériques coexistant chez un même hôte ne sont pas retrouvés chez les lièvres. Cette exception est attribuée aux moeurs solitaires de l’hôte et au polyphylétisme très vraisemblable du genre Eimeria. Les données paléontologiques sur les Leporidés indiquent que les parasites des lapins dérivent de ceux du lièvre.